MHEALTH FOR HIGH-RISK PREGNANCIES IN DEVELOPING COUNTRIES: A SCOPING REVIEW - Padmaningtyas, Dewi Anggraini; Hidayat, Asri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
This study explores the application of mHealth technologies in antenatal care for high-risk pregnancies in developing countries, emphasizing their potential to enhance maternal health service quality. By leveraging the PRISMA-ScR checklist and PCC framework, a scoping review of 858 articles from PubMed, ScienceDirect, EBSCO, and Google Scholar identified 13 relevant studies. Key themes include the types of mHealth utilized (mobile apps, SMS, phone calls, and web-based platforms), their benefits (screening, monitoring, health education, and complication reduction), improvements in antenatal care (innovative care models, increased visit frequency, reduced risks, and better pregnancy outcomes), and their role in supporting high-risk pregnancies (emotional support, risk education, and clinical decision-making). The findings highlight mHealth's potential to address healthcare disparities and provide cost-effective solutions in resource-constrained settings. Moreover, mHealth offers promising contributions to achieving maternal health-related Sustainable Development Goals (SDGs) by 2030, notably by improving access to quality care, reducing maternal and neonatal risks, and mitigating healthcare inequities. However, further research is required to evaluate the long-term effects, scalability, and sustainability of mHealth initiatives in the developing countries.  Keywords: Mobile Health; Telemedicine; Maternal Health; High-Risk Pregnancy; Developing Countries